2022
DOI: 10.3390/insects13100956
|View full text |Cite
|
Sign up to set email alerts
|

Biological Parameters, Phenology and Temperature Requirements of Halyomorpha halys (Hemiptera: Pentatomidae) in the Sub-Mediterranean Climate of Western Slovenia

Abstract: In the last decade, the invasive brown marmorated stink bug Halyomorpha halys, native to East Asia, has become one of the most serious pests for agricultural crops worldwide. First detected in Europe (in Switzerland), the insect is now widely found across the European continent and many Eurasian countries. Since its first appearance in Slovenia in 2017 it has caused considerable damage to fruit and vegetable production. Understanding the biology and behavior in the local environmental conditions is of key impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
(75 reference statements)
2
8
0
Order By: Relevance
“…On the other hand, it was observed that overwintering BMSB adults laid eggs until the end of August in this study, as well as in some other studies in Türkiye (unpublished). (Rot et al 2022) In all the studies mentioned, it was observed that the first-generation adults produced fewer egg masses compared to overwintering adults, similar to some other countries. According to some researches (Nielsen and Hamilton, 2009a;Nielsen et al 2016;Costi et al 2017), the adult stages of two generations may overlap in field.…”
Section: Development Times Of Biological Stages Of Halyomorpha Halyssupporting
confidence: 57%
See 4 more Smart Citations
“…On the other hand, it was observed that overwintering BMSB adults laid eggs until the end of August in this study, as well as in some other studies in Türkiye (unpublished). (Rot et al 2022) In all the studies mentioned, it was observed that the first-generation adults produced fewer egg masses compared to overwintering adults, similar to some other countries. According to some researches (Nielsen and Hamilton, 2009a;Nielsen et al 2016;Costi et al 2017), the adult stages of two generations may overlap in field.…”
Section: Development Times Of Biological Stages Of Halyomorpha Halyssupporting
confidence: 57%
“…While overall mortality of nymphs in the first generation was 22.97%, it was 90.24% in the second generation (Table 1). Similarly, Rot et al (2022) reported that the overall mortality rate in the first generation ranged between 25.07 and 78.57%, and that it ranged between 31 to 100% in the second generation. Haye et al (2014) and Costi et al (2017) reported that total mortality and mortality rates for nymphal stages demonstrated significant differences in the first and second generation, which is consistent with our findings (Tablo 1).…”
Section: Egg Hatching and The Mortality Rates Of Developmental Stagesmentioning
confidence: 88%
See 3 more Smart Citations